Characterization of toxin-antitoxin systems from public sequencing data: A case study in Pseudomonas aeruginosa - Dai, Zehan; Wu, Tianzhi; Xu, Shuangbin; Zhou, Lang; Tang, Wenli; Hu, Erqian; Zhan, Li; Chen, Meijun; Yu, Guangchuang (Frontiers in Microbiology, 2022)
The toxin-antitoxin (TA) system is a widely-distributed group of genetic modules playing important roles in the life of prokaryotes, it's association with MGE contributing the antibiotic resistance gene (ARG) dissemination has been drawing attention. The diversity and richness of TA systems in Pseudomonas aeruginosa, as one of the bacteria species with ARGs, have not yet been completely demonstrated, especially the non-type-II TA systems. In this study, we explored the TA systems from both the public genomic sequencing data and genome sequences. A small scale of genomic sequencing data in 281 isolates were selected from NCBI SRA database, reassembling the genomes of these isolates led to the identification of numerous abundant TA homologs. Further, remapping these identified TA modules on 5437 genome/draft genomes uncover a great diversity of the type II TA modules in P. aeruginosa. Further manual inspection revealed several TA systems which were not yet reported in P. aeruginosa including the hok-sok of type I system, cptA-cptB system, and cbeA-cbtA system of type IV system. Additional annotation revealed that a large number of mobile genetic elements (MGE) , were closely distributed with TA. Also 16% of ARGs locate relatively close to TA. Our work confirmed a wealth of TA genes in the unexplored P. aeruginosa pan-genomes, expanded the knowledge on P. aeruginosa, and provided methodological tips on large-scale data mining for future studies. The co-occurrence of MGE, ARG and TA may indicate that a potential interaction of the three in their dissemination.